Incidence, mortality, and economic burden of myasthenia gravis in China: A nationwide population-based study - Chen, Jingshan (Lancet Reg Health West Pac, 2020)
BACKGROUND: Myasthenia gravis (MG) is the most common primary disorder of neuromuscular transmission, but the incidence of MG in China is unknown. We conducted the first nationwide study to determine the incidence and mortality rates of MG in all age groups at the national level in China. METHODS: This national population-based registry study is based on the database of the Hospital Quality Monitoring System of National Health Commission, which covers 1665 hospitals providing myasthenia gravis care in 31 provinces and municipalities across China. 94,638 hospital admissions for 59,243 myasthenia gravis patients were identified from January 1st, 2016 to December 31st, 2018. Myasthenia gravis was identified by ICD-10 codes (G70). Incidence of myasthenia gravis was stratified by age, sex, and province. FINDINGS: Of 59,243 patients, 30,503 individuals with myasthenia gravis were newly diagnosed. Age and sex adjusted incidence of myasthenia gravis was 0.68 per 100,000 person-years, with highest in the age group of 70–74 years. The incidence in females was 0.76 per 100,000 and 0.60 per 100,000 in males. The admission mortality rate was 14.69‰. Respiratory failure was the leading cause of death in patients with myasthenic crisis. There were 14,840 patients with thymomas, encompassing 14,636 (26.5%) adults and 204 (7.1%) juveniles. 9453 (63.7%) patients with thymomas underwent thymomectomy. The median length of hospital stay was 8 days (interquartile range (IQR) 4 to 15 days) with median hospitalization cost $1037 (IQR $493 to $2925). The Basic Medical Insurance was the most common payment method, covering 67.4% of patients. INTERPRETATION: The age and sex adjusted incidence of MG was 0.68 per 100,000 person-years in China. The admission mortality rate was 14.69‰. Most cases of new onset MG occurred in the seventh decade of life. FUNDING: National Science Foundation of China (91642205, and 81830038); Advanced Innovation Center for Human Brain Protection, Capital Medical University, Beijing